Kandungan Nutrisi Rumput Laut (Eucheuma cottonii) dengan Metode Rakit Gantung pada Kedalaman Berbeda - Budiyanti; Supasman Emu (AquaMarine (Jurnal FPIK UNIDAYAN ), 2021)
The nutrition content of seaweed in the form of agar, carrageenan, and algin caused seaweed had an important meaning in industry. One type of seaweed that can be used as food ingredients was the type of seaweed Eucheuma cottonii (Aslan, 1991 in Khasanah, 2013). E. cottonii seaweed can be used as a source of nutrition because it generally contains carbohydrates, protein, a little fat and ash which are mostly salt compounds such as sodium and calcium. Seaweed can grow well and got high quality if cultivated at the appropriated depth location. This study aims to determined the effect of hanging raft placement at different depths on the nutrient content of seaweed Eucheuma cottonii. The material used in this study was Eucheuma cottonii seaweed obtained from seaweed farmers in the waters of Doda Bahari Village, Sangia Wambulu District, Central Buton Regency. The raft used is 4 x 2 meters in size. The experimental design used in this study was Randomized Design Group (RAK). Grouping was done based on the distance from the lowest low tide coastline with different depth treatments, namely Group I: Location (Starting from the lowest receding coastline) with depth (A) 0.5 m, (B) 1 m, and (C) 2 m. Group II: Location (100 meters from lowest ebb) with depth (A) 0.5 m, (B) 1 m, (C) 2 m. Group III: Location (100 meters from Group 2) with depth 0.5 m (A), (B) 1 m, (C) 2 m. To find out the difference number of Eucheuma cottonii nutritional performed statistical tests Of Variant analysis (ANOVA) was performed used the SPSS application. If it was significantly different, proceed with the Smallest Significant Difference test (BNT) (Steel and Torrie, 1993). Whereas water quality supporting data such as temperature, salinity, brightness, current speed, pH, nitrate and phosphate were analyzed descriptively. The results showed that the nutrient content of seaweed (Protein, Fat and Carbohydrate content had no significant effect on the hanging raft placement at a depth of 0.5 meters, 1 meter and 2 meters. Water quality during the study was still in a reasonable range.